Re "International survey on skin patch test procedures, attitudes and interpretation" L.K. Tanno et al., WAOJ (2016) 9:8 - Uter, Wolfgang; Bruze, Magnus; Rustemeyer, Thomas; Orton, David; Mahler, Vera (World Allergy Organization Journal, 2017)
A previous survey on the practice of diagnostic patch testing among representatives of member societies of the World Allergy Organization (WAO) has, in some countries, not addressed those stakeholders actually involved in patch testing, mainly dermatologists. The need for further standardisation is acknowledged and has been addressed e.g. by publication of a patch test guideline by the European Society of Contact Dermatitis in October 2015.
EVALuna2:34194